Synthesis and Biological Activity of Some 2,5-Disubstituted 1,3,4-Oxadiazoles - Alam, Ozair; Gupta, S.K.; Imran, Mohd.; Khan, S.A. (Asian Journal of Chemistry, 2016)
Some new 2-(coumarin-3-yl)-5-aryl-1,3,4-oxadiazols (IIIa-h) were synthesized by reacting hydrazide II of 3-carbethoxycoumarin (I) with various aromatic acids in presence of phosphorus oxychloride. Their elemental, IR and 1H NMR data characterized these oxadiazoles. All the compounds were tested for their analgesic and antimicrobial activity against S. aureus, E. coli and C. albicans. Compounds IIIb, IIIc and IIIf exhibited interesting results.